Analisis Akurasi ChatGPT dalam Mengkaji Validitas Sanad dan Matan Hadis - Amalia, Yeni (Journal of Hadith Studies, 2024)
The emergence of ChatGPT as a new technology capable of addressing various religious issues, particularly in Hadith studies, presents new challenges for Hadith scholars in preserving the authenticity and sanctity of Hadith. This study aims to evaluate the accuracy of ChatGPT in assessing the validity of sanad and matan by comparing its analysis of five selected hadiths with the book Jawami’ul Kalim. Using a descriptive-analytical method, the research refers to the concept of "Rules for the Validity of Sanad Hadith" by Syuhudi Ismail. The findings reveal that while ChatGPT can provide preliminary analysis on the validity of hadiths, its evaluation is limited to the information available in its database. The analysis tends to be descriptive and lacks the depth found in Jawami’ul Kalim. ChatGPT's understanding of ulumul hadith is inconsistent, often producing incorrect or unverified answers, and it fails to cite reliable sources. In contrast, Jawami’ul Kalim offers more comprehensive and accurate takhrij with credible references. Therefore, while ChatGPT shows potential as a supportive tool in Hadith studies—especially in early-stage exploration—it cannot replace scholars or classical references. Expert guidance remains essential to ensure the accuracy and reliability of its assessments.